2014
DOI: 10.1371/journal.pone.0098206
|View full text |Cite
|
Sign up to set email alerts
|

Response of Rocky Reef Top Predators (Serranidae: Epinephelinae) in and Around Marine Protected Areas in the Western Mediterranean Sea

Abstract: Groupers species are extremely vulnerable to overfishing and many species are threatened worldwide. In recent decades, Mediterranean groupers experienced dramatic population declines. Marine protected areas (MPAs) can protect populations inside their boundaries and provide individuals to adjacent fishing areas through the process of spillover and larval export. This study aims to evaluate the effectiveness of six marine reserves in the Western Mediterranean Sea to protect the populations of three species of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 58 publications
1
47
1
Order By: Relevance
“…As a result, size distribution is highly skewed towards small and medium-sized individuals, a situation commonly observed in other unprotected areas (e.g. Di Franco et al, 2009;La Mesa et al, 2010;Hackradt et al, 2014). The effect of intense fishing pressure and other forms of human disturbance was particularly evident in sectors I, V and VI, where no large individuals belonging to the target species were recorded.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As a result, size distribution is highly skewed towards small and medium-sized individuals, a situation commonly observed in other unprotected areas (e.g. Di Franco et al, 2009;La Mesa et al, 2010;Hackradt et al, 2014). The effect of intense fishing pressure and other forms of human disturbance was particularly evident in sectors I, V and VI, where no large individuals belonging to the target species were recorded.…”
Section: Discussionmentioning
confidence: 86%
“…The increase in density and mean size of individuals of overexploited species, along with recolonization of shallower habitats, are among the most evident and documented effects of protection within MPAs (La Côté et al, 2001;García-Charton et al, 2004;Claudet et al, 2006;Guidetti & Sala, 2007;Lester et al, 2009;Aburto-Oropeza et al, 2011;Guidetti et al, 2014;Hackradt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, declines can occur if the fishing effort displaced by reserves leads to increased mortality that outweighs the amount of spillover (Karnauskas et al 2011, Rassweiler et al 2012. Overall, the typical expected (Kellner et al 2008, Pelc et al 2010, White et al 2011 and observed (e.g., Hackradt et al 2014, Willis et al 2003) spatial distribution of abundance peaks within reserves and declines toward the reserve boundaries, depending on the spatial pattern of fishing in harvested areas (e.g., concentration of fishing effort near reserve boundaries; see Kellner et al 2007). The current standard for empirical inference of reserve-driven population responses is a before-after control-impact design-in other words, measurement of populations both inside and outside a reserve and before and after reserve establishment, which can control for the effect of environmental variability on population changes in time and the effect of habitat quality on population differences in space (Guidetti 2002, Jennings 2000.…”
Section: Response To Heterogeneity In Space and Timementioning
confidence: 97%
“…With respect to the latter, growth rate is set to constant both in the absence and presence of fishing, and mortality from fishing is also set to be proportional with fish biomass in unprotected areas. Consequently, density is assumed to be below carrying capacity in the MPAs (Hackradt et al, 2014;Karakassis et al, 2013). The lack of age-structured population dynamics may be defended for species with a natal dispersal rate that is smaller than the adult dispersal rate (Ronce et al, 1998).…”
Section: Limitations and Simplifications Of The Methodsmentioning
confidence: 99%